As quitandadeiras de Minas Gerais: memórias brancas e memórias negras - Javier Alejandro Lifschitz; Juliana Bonomo (Ciências Sociais Unisinos)
In this article, we analyze narratives of memory about homemade pastries (quitandas) and the women who make them (quitandeiras) in the state of Minas Gerais, in three historical moments: as practices of African origin, which during the eighteenth and nineteenth century was reproduced in the colonies by black slave women selling food on the streets, carrying their trays; as practices of Portuguese origin, held within farms domestic black slaves under the supervision of white mistresses of Portuguese origin and, finally, as current policy of cultural heritage. We try to identify, based on secondary material and interviews, which social memory we have today on this feminine craft that pervaded different social and ethnic groups, and how local authorities started to intervene in its construction.